Optically functional isoxanthopterin crystals in the mirrored eyes of decapod crustaceans - Palmer, Benjamin A. (Proc Natl Acad Sci U S A, 2018)
The eyes of some aquatic animals form images through reflective optics. Shrimp, lobsters, crayfish, and prawns possess reflecting superposition compound eyes, composed of thousands of square-faceted eye units (ommatidia). Mirrors in the upper part of the eye (the distal mirror) reflect light collected from many ommatidia onto the photosensitive elements of the retina, the rhabdoms. A second reflector, the tapetum, underlying the retina, back-scatters dispersed light onto the rhabdoms. Using microCT and cryo-SEM imaging accompanied by in situ micro–X-ray diffraction and micro-Raman spectroscopy, we investigated the hierarchical organization and materials properties of the reflective systems at high resolution and under close-to-physiological conditions. We show that the distal mirror consists of three or four layers of plate-like nanocrystals. The tapetum is a diffuse reflector composed of hollow nanoparticles constructed from concentric lamellae of crystals. Isoxanthopterin, a pteridine analog of guanine, forms both the reflectors in the distal mirror and in the tapetum. The crystal structure of isoxanthopterin was determined from crystal-structure prediction calculations and verified by comparison with experimental X-ray diffraction. The extended hydrogen-bonded layers of the molecules result in an extremely high calculated refractive index in the H-bonded plane, n = 1.96, which makes isoxanthopterin crystals an ideal reflecting material. The crystal structure of isoxanthopterin, together with a detailed knowledge of the reflector superstructures, provide a rationalization of the reflective optics of the crustacean eye.